Controlling Cryptosporidium in the environment. (13th June 2015) - Wells, Beth
Abstract : Cryptosporidium: is a zoonotic pathogen which can affect livestock, wild animals and people. If public water supplies become contaminated with the parasite, it can pose a public health risk. Recently, Beth Wells and colleagues from the Moredun Research Institute undertook a study looking at Cryptosporidium transmission in Glenlivet, Scotland. The project provided an example of how the health of livestock, wild animals, the environment and people intersect